Diffusion modeling in cemented carbides: Solubility assessment for Co, Fe and Ni binder systems. (November 2017) - Walbrühl, Martin; Linder, David; Ågren, John; Borgenstam, Annika
Abstract: The increasing interest in alternative binder solutions for WC based cemented carbide systems leads to more integration of ICME (Integrated Computational Materials Engineering) based concepts in the materials development. This work investigates the non-equilibrium W and C solubilities upon furnace-cooling in a wide range of Co and Fe-Ni based binder systems by computational means. It is shown that the solubilities strongly depend on the C-activity and binder matrix elements, revealing that Ni dissolves most W and Fe most C out of the investigated systems. Furthermore, the effect of the binder mean free path and the cooling rates on the solubilities was investigated. The presented method and results provide insights to control the binder chemistry and will help to design the properties for future binder systems in a fast and efficient way. Highlights: A general method is provided to compute non-equilibrium solubilities in cemented carbide binder systems. The non-equilibrium solubilities are calculated for W and C in Co, Fe and Ni binders using DICTRA. Effects of the C-activity, binder thickness and cooling rate on the non-equilibrium solubilities are investigated.